Perancangan Sistem Informasi Pos Pelayanan Terpadu Apel Merah Kelurahan Jati Padang Berbasis Website - Randi Sudandi; Ferdian Achmad Rizki; Ari Apriyani; Rachman Komarudin (ZETROEM, 2023)
Integrated Health Post (Posyandu) is one form of Community-Based Health Effort (CBHE) managed by, for, and together with the community, aimed at empowering and providing facilities to the community in obtaining healthcare services for mothers, infants, and toddlers. The challenges faced by Posyandu Apel Merah include the manual recording of data, which is done by hand using shortcut books to document the activities of the Posyandu. The purpose of this research is not only to fulfill the requirements for our literature degree but also to assist Posyandu cadres in simplifying the recording of Posyandu activities using the system we are developing, called "Sahabat Posyandu." The research method we employed involved interviews and data collection conducted with the chairwoman of Posyandu Apel Merah, Mrs. Saimah herself. The results of our research will be implemented into the system we are building to aid Posyandu cadres in recording data related to weight measurements and pregnant women. The system we are developing is titled "Sahabat Posyandu: Integrated Post Service Information System for Apel Merah Subdistrict, Jati Padang, Based on a Website. Keywords: Information System, Integrated Service Center, Website